Severe anemia on the treatment of a Lepra patient with a history of long-term steroid consumption suspect of Cushing syndrome - Gede Padmawijaya; Andi Ridwan Jalal; Zakaria Mustari (Universitas Muhammadiyah Surabaya, 2022)
ABSTRACT Anemia is a clinical symptom caused by the disruption of erythrocyte formation, bleeding, and premature blood hemolysis. Severe anemia can occur in patients taking dapsone for the treatment of leprosy. Long-term use of steroids is also a predisposing factor for the occurrence of hematological changes and raises the suspicion of Cushing's syndrome. Reportedly a 20-year-old woman with the main complaint of sudden shortness of breath, accompanied by a cough with phlegm. The patient has had a history of multibacillary type leprosy since a month ago. There was a history of steroid consumption for about two years and only stopped a couple of months ago. Physical examination showed the oxygen saturation was 93%, conjunctival anemia, hyperpigmented plaques, tenderness in the abdominal, meteorism, and pitting edema in the upper and lower extremities. Laboratory examination revealed hemoglobin (Hb) level 2.4 mg/dl, erythrocytes 0.8x106/ul, and albumin 3.2g/dl. Peripheral blood smear results suggest refractory anemia and myelodysplasia syndrome. After being treated for seven days, the patient was re-evaluated and controlled at the Internal Medicine outpatient clinic, Syekh Yusuf Hospital. Complex symptoms and limited investigations make it difficult to establish the exact cause. Immediate blood transfusion and management of the underlying disease causing anemia, such as discontinuation of dapsone, are the primary management of this case. Keywords : severe anemia, leprosy, steroid, Cushing syndrome.Correspondence : gedepadmawijaya@yahoo.com